Pemilihan Desain Prosthetic Jari Tangan Berdasarkan Mekanisme Sistem Penggerak Cross Bar dan Cross Cable terhadap Besar Gaya Tarik Dinamis Prosthetic Jari Tangan - Susy Susmartini; Ilham Priyadithama; Lobes Herdiman (Performa: Media Ilmiah Teknik Industri, 2011)
The absence of the hand causes the disruption of organ function, this problem later emerged prosthetic as a tool for replacement of missing body parts. Basically prosthetic hand has two functions: as cosmetics and as a functional tool. The most important functional aspects of prosthetic hands is the ease of operation that can be seen from the magnitude of tensile force required by prosthetic hand while doing the a movement. The mechanism of motion system that is widely used by prosthetic hand is a cross cable system and cross bar system. Cross cable systems using cable to connect components that act as links knuckles on hand, when the withdrawal event of the cable happened, the cable will be tightened and the movement of the fingers may occur. Cross bar systems uses bar (rigid link) as a puller, so when withdrawal event of the rope at the end of the lever happened, the bar that connects the components with a finger lever puller will push or pull bar so that the finger will open or close. Prosthetic design significantly influence the magnitude of the dynamic tensile strength that makes it necessary to make an experiments to compare the design of motion mechanisms of cross cable systems and cross bar system, and evaluate the influence on the magnitude of the dynamic tensile force at the time of movement, so it can represent the natural movement of normal human fingers.